Navigating the Limits of Capitalism to Resist Urban Marginality: The Case of the Casa Madiba Network - Rauleac, Greta (PARTECIPAZIONE E CONFLITTO, 2020)
This empirical paper addresses a key problem for activists: how to resist capitalism while simultaneously responding to the immediate needs of the most marginalized segments of the population. Through the analysis of the case of Casa Madiba, a social center in Rimini (Italy), the paper discusses the role of squatting and the temporary use of space in the formation of the urban commons. It presents community-led urban development projects and bottom-up forms of welfare as potential tools to create a vision of the world that systematically opposes neoliberalism. It also considers some potential risks squatters face. Squatting has often been used as a placeholder by real estate investors or by the municipality, and even has the potential to be co-opted into master planning. The paper shows how squatters located in smaller towns can strategically adapt to the local social geography by creating strategic alliances which incorporate the tradition of partisan mutual help and social welfare in their day-to-day practice.